2020
DOI: 10.1136/bmjopen-2019-035471
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and triggers of incivility within healthcare teams: a systematic review of the literature

Abstract: ObjectivesTo explore predictors and triggers of incivility in medical teams, defined as behaviours that violate norms of respect but whose intent to harm is ambiguous.DesignSystematic literature review of quantitative and qualitative empirical studies.Data sourcesDatabase searches according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline in Medline, CINHAL, PsychInfo, Web of Science and Embase up to January 2020.Eligibility criteriaOriginal empirical quantitative and qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(127 citation statements)
references
References 84 publications
5
119
0
3
Order By: Relevance
“…29 Additionally, it has been theorized that that when faced with unchecked incivility in the workplace, they are more likely to withdraw from work and work‐related tasks, a behavior not seen as often in males. 30 The disproportionate exposure of females to incivility, 10 in frequency (as was the case in this study) or along with other concomitant discrimination, may play a role in the sex‐based differences seen in response to incivility. The discrepancies identified in our study warrant further scrutiny to help ensure a positive environment for all trainees, regardless of sex.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…29 Additionally, it has been theorized that that when faced with unchecked incivility in the workplace, they are more likely to withdraw from work and work‐related tasks, a behavior not seen as often in males. 30 The disproportionate exposure of females to incivility, 10 in frequency (as was the case in this study) or along with other concomitant discrimination, may play a role in the sex‐based differences seen in response to incivility. The discrepancies identified in our study warrant further scrutiny to help ensure a positive environment for all trainees, regardless of sex.…”
Section: Discussionmentioning
confidence: 63%
“…Of the eight studies focused on physicians, only three included trainees and none were focused on trainee–trainee interactions. 10 Our study sought to examine incivility between resident physicians in EM and ophthalmology. While EM physicians are represented to a small extent in the literature, to our knowledge, there are no studies looking at incivility among ophthalmology physicians or trainees in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past study conducted by Smith and Morin, (2018) also indicated incivility received from work environment leads employee to engage in antisocial attitude that comes with financial obligation for the company. Thus, co-worker incivility is considered as one of the important triggering factors that promotes employees' negative attitude (Keller & Yule, 2020). This research provide and evidence that Coworker incivility is prevailing in casual dining restaurants and there is lack of tanning facilities for front line employees.…”
Section: Figure 1: Illustration Of Moderating Influence Of Emotional mentioning
confidence: 71%
“…Rather, patients/visitors are commonly discussed in an indirect way. Many studies have discussed how incivility among health care providers may have downstream consequences on patient safety and health outcomes ( 17 , 18 ). Other studies have documented incivility and other forms of mistreatment toward patients, but through the lens of health care providers ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%